Risk in the economic system and its characteristics (Eurasian Research Bulletin, 2026)
This article examines the methodological foundations of tax risk assessment and management in the tax system. The issues of improving tax administration in the digital economy and analyzing taxpayers' activities based on a risk-oriented approach are discussed. The article considers the criteria for identifying tax risks and models for their quantitative assessment, and puts forward proposals to improve the effectiveness of risk management in the tax system of Uzbekistan.